A checklist of the forest and forest edge birds of the Padang-Sugihan Wildlife Reserve, South Sumatra - Nash, Stephen V; Nash, Anne D (KUKILA, 1985)
The following is a checklist of the resident and migrant species found in and beside the forested parts of the Padang-Sugihan Wildlife Reserve, South Sumatra Province.